Do People Regard Robots as Human-Like Social Partners? Evidence From Perspective-Taking in Spatial Descriptions - Xiao, Chengli; Xu, Liufei; Sui, Yuqing; Zhou, Renlai (Frontiers in Psychology, 2021)
Spatial communications are essential to the survival and social interaction of human beings. In science fiction and the near future, robots are supposed to be able to understand spatial languages to collaborate and cooperate with humans. However, it remains unknown whether human speakers regard robots as human-like social partners. In this study, human speakers describe target locations to an imaginary human or robot addressee under various scenarios varying in relative speaker-addressee cognitive burden. Speakers made equivalent perspective choices to human and robot addressees, which consistently shifted according to the relative speaker-addressee cognitive burden. However, speakers' perspective choice was only significantly correlated to their social skills when the addressees were humans but not robots. These results suggested that people generally assume robots and humans with equal capabilities in understanding spatial descriptions, but do not regard robots as human-like social partners.